AGENCY COSTS AND COMPANY PERFORMANCE IDX 30 - Linda; Raida Fuadi; Wida Fadhlia; Gamal Batara (Jurnal Magister Akuntansi Trisakti, 2023)
This study aims to examine the levels of corporate agency costs for high- and low-value companies listed on Indonesia Stock Exchange_30 (IDX30) during the Covid-19 pandemic, and then analyze the impact of corporate governance and debt on corporate performance, mediated by agency cost variables. The average expense ratio and asset utilization ratio values are used as the basis for determining high or low agency costs in the IDX30 Indonesia companies. Partial least squares structural equation modelling (Partial Least Square-Structural Equation Model) analysis is used to analyze the effect of corporate governance and debt on firm performance mediated by agency cost variables. The results indicate that the average agency costs in IDX30 companies are low. Corporate governance significantly affects the level of agency costs and firm performance. While the direct effect of debt on firm performance is not significant, its effect on firm performance mediated by low agency costs shows a significant relationship.